Prevención de incendios y explosiones en empresas agroindustriales - Orozco, Hitler (2010)
This paper gives an overview about the electrical hazards that may be caused by fire and / or explosions in an agribusiness. For our study we start from Piladora rice, which made an analysis of electrical installations, based on the different rules for preventing fires and explosions. Risk indexes were calculated by the method of FRAME, the guide gave us a quantitative risk of fire exists in the operation of agribusiness, calculating the risk for the development, processes and people.